2012
DOI: 10.1007/s11596-012-0065-z
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of microRNA-34a on cell migration and invasion of invasive urothelial bladder carcinoma by targeting notch1

Abstract: MicroRNAs (miRNAs or miRs) are a class of short, non-coding RNAs that participate in various oncological processes. This study aims to explore the roles of microRNA-34a (miR-34a) in invasive urothelial bladder carcinoma. miR-34a was transfected into bladder cancer cell lines 253J and J82. The miR-34a expression levels in tissues and cells were detected by using qRT-PCR. The Notch1 expression was detected by qRT-PCR and Western blotting. Cell migratory and invasive abilities were measured by Transwell chamber a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 33 publications
4
30
0
Order By: Relevance
“…Transfections were performed with Mega-Tran 1.0 transfection reagent (OriGene, USA) as previously described. [16] To perform luciferase assay, 1×10 5 HUVEC-C cells were transferred to 24-well plates and cultured for 24 hours. Then, miR-30a (0.6 µg) or negative control (0.6 µg) was co-transfected with DLL4 3′UTR plasmid (0.2 µg) and pRL-TK plasmid (0.05 µg) for 48 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Transfections were performed with Mega-Tran 1.0 transfection reagent (OriGene, USA) as previously described. [16] To perform luciferase assay, 1×10 5 HUVEC-C cells were transferred to 24-well plates and cultured for 24 hours. Then, miR-30a (0.6 µg) or negative control (0.6 µg) was co-transfected with DLL4 3′UTR plasmid (0.2 µg) and pRL-TK plasmid (0.05 µg) for 48 hours.…”
Section: Methodsmentioning
confidence: 99%
“…A growing body of evidence indicates that aberrant regulation of miRNAs is associated with bladder cancer progression and metastasis. For example, multiple miRNAs including miR-34a, miR-133, miR-493, miR-582, miR-1280, and miR-1826 have been implicated in the suppression of metastasis by functioning as tumor-suppressor genes Majid et al, 2012;Uchino et al, 2013;Ueno et al, 2012;Zhang et al, 2012;Zhou et al, 2012;). In addition, a microRNA expression ratio may have the ability to distinguish between invasive and noninvasive bladder tumors with high sensitivity and specificity (Neely et al, 2010;Wszolek et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, previous studies have indicated that miR-34a inhibits migration and invasion via Notch1 and CD44 and induces chemosensitivity to cisplatin treatment, regardless of the p53-Rb pathway in bladder cancer [12,31,32]. In the present study, BIU87/ADR was obtained from BIU87 through treatment with EPI.…”
Section: Discussionmentioning
confidence: 85%